Digital Image Processing using SCILAB - Thanki, Rohit M.; Kothari, Ashish M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides basic theories and implementations using SCILAB open-source software for digital images. The book simplifies image processing theories and well as implementation of image processing algorithms, making it accessible to those with basic knowledge of image processing. This book includes many SCILAB programs at the end of each theory, which help in understanding concepts. The book includes more than sixty SCILAB programs of the image processing theory. In the appendix, readers will find a deeper glimpse into the research areas in the image processing.
Introduction -- Digital Image Fundamentals -- Image Enhancement in Spatial Domain Filtering in the Frequency Domain -- Image Restoration and Reconstruction -- Color Image Processing -- Image Compression -- Image Segmentation -- Morphological Image Processing -- Advanced Applications of Image Processing -- Conclusion.
Keywords: Signal processing; Computer vision; Control engineering; Robotics; Automation; Artificial intelligence; Signal, Speech and Image Processing .; Computer Vision; Control, Robotics, Automation; Artificial Intelligence